Prostatic carcinoma whose initial manifestation was a tumor of external auditory canal - Tadashi Terada, MD, PhD (Elsevier, 2016)
Background: Metastatic carcinoma manifesting as a mass in external auditory canal (EAC) is very rare, and prostatic adenocarcinoma (PA) presenting firstly as a mass of EAC has not been reported. Aim: To report a case of PA manifesting as only a mass of EAC. Case report: A 77-year-old man presented a right EAC mass. Otoscope identified a small mass approximately 7 mm in right EAC neat to the external orifice. Biopsy showed well differentiated adenocarcinoma with cribriform appearances. The author highly suspected metastatic prostatic PA (Gleason 4 + 4 = 8) and performed an immunohistochemical (IHC) study. The IHC showed positive prostate-specific antigen, prostatic acid phosphatase, alpha-methylacyl-CoA racemase, cytokeratin (CK) 7, and CK20. The tumor was negative for TTF-1, CDK2, and NCAM. The definite diagnosis of PA metastatic to EAC was made. The patient was referred to Urology and prostatic needle biopsy showed PA with immune-expressions of PSA, PAP, and AMACR. Serum PSA was high (63 ng/L). Imaging techniques showed a few metastases in bones of vertebula and ribs. The skull appeared free of metastasis, and head and neck soft tissue showed no metastatic areas except for the shadow of EAC. The patient is now treated with hormone and chemotherapy. Conclusion: The first case of an EAC mass that is a metastatic lesion of prostatic adenocarcinoma, was reported.